Determinants of Firm Value: The Role of Sales Growth, Capital Structure, and Liquidity - Azmi Makarim Nur Islami; Nastiti Rizky Shiyammurti (Universitas Muhammadiyah Makassar, 2026)
The coal mining industry plays a strategic role in Indonesia’s economy but is highly exposed to global commodity price volatility, creating uncertainty in firm value. Despite extensive research on firm value determinants, empirical findings remain inconsistent, particularly within volatile extractive industries in emerging markets. This study aims to examine the effects of sales growth, capital structure, and liquidity on firm value in coal mining companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This study adopts a quantitative approach using panel data regression analysis. The sample consists of 27 companies selected through purposive sampling, resulting in 120 firm-year observations after outlier adjustment. Firm value is proxied by Price to Book Value (PBV), while sales growth, capital structure (Debt-to-Equity Ratio), and liquidity (Current Ratio) serve as independent variables. The Fixed Effect Model (FEM) is employed as the most appropriate estimation model. The results indicate that, simultaneously, sales growth, capital structure, and liquidity significantly affect firm value. However, partially, only capital structure shows a positive and statistically significant effect, while sales growth and liquidity are found to be insignificant. These findings suggest that investors place greater emphasis on financing decisions rather than operational growth or short-term financial stability in assessing firm value within a highly volatile industry. This study contributes to the literature by providing sector-specific evidence and refining signaling theory, demonstrating that the effectiveness of financial indicators as signals is context-dependent. The findings offer practical implications for managers, investors, and policymakers in formulating more resilient financial and investment strategies.